Legislative Effectiveness: The legislative performance of house representatives of the 16th Philippine Congress - Joanna Marie Baroman (Diversitas Journal)
Policymakers’ legislative performances guide constituents for informed electoral choices. However, the lack of empirical inquiry on the legislative effectiveness of the members of the House of Representatives in the Philippines subjected constituents to rely on 'self-legislative' reporting among incumbents seeking re-election. This study aims to determine the legislative effectiveness of the House members of the 16th Congress using their primary authored bills. Utilizing the Legislative Effectiveness Model (LEM), the sponsored bills are weighted and computed to become the individual member's Legislative Effectiveness Score (LES). The study further investigated variables that affect the legislative effectiveness of House representatives. Results revealed that during the 16th Congress, House members filed an average of 24 bills within the three-year term. Additionally, each member's legislative effectiveness is improved by chairmanship to legislative committees, either standing or special. The study concluded that the 16th Congress House of Representatives comprises policymakers who are averagely effective in pushing for policy preferences into the legislative process and to laws.